China’s Maritime Silk Road: Strategic Containment or Economic Connectivity - Gupta, Aman; Kumar, Yash (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
A key component of the Belt and Road Initiative (BRI), China's Maritime Silk Road (MSR) has become a revolutionary force in regional connectivity, international trade, and geopolitical strategy. The conflict between strategic containment and economic connectedness is the main subject of this paper's critical analysis of the MSR's dual nature. China's port investments in South Asia, East Africa, and Europe, including Gwadar, Hambantota, Djibouti, and Piraeus, are examined to determine how these infrastructure projects simultaneously improve trade facilitation and expand China's maritime influence to attract tourists. The strategic consequences are highlighted by the realist viewpoint, which also depicts India's possible hold and the projection of naval might through overseas bases and dual-use facilities. The liberal perspective also emphasizes the economic advantages of increased commerce, interdependence, and regional integration, which provide host countries with chances for growth and shared incentives. Constructivist insights show that policy responses are shaped by regional narratives and perceptions, with some nations welcoming Chinese investments for economic growth while others see them as security risks. Additionally, the article discusses the MSR's operating limitations, environmental issues, debt dependency, and geopolitical tensions. This paper offers a sophisticated grasp of the MSR's complex goals and ramifications by utilizing a multidisciplinary theoretical framework. In the end, the study makes the case that the MSR is a complex synthesis of strategic and economic goals that will influence the political and economic climate of the Indo-Pacific in the ensuing decades rather than being boiled down to a single narrative of containment or connectedness.